Retinal nitric oxide and malonyldialdehyde levels following photodynamic therapy - Turkcuoglu, Peykan; Ozturkmen, Cem; Ilhan, Nevin; Kurt, Julide; Aydemir, Orhan; Celiker, Ulku; Rashid, Aymen (Medknow Publications & Media Pvt Ltd, 2011)
Background:To determine the retinal nitric oxide (NO) and malonyldialdehyde (MDA) levels following photodynamic therapy (PDT). Materials and Methods:Seven Dutch-belted rabbits received dextrose, while seven others received 2 mg/kg verteporfin infusion over a period of 15 minutes in a dim-lit room. Irradiation to a 1.5 mm diameter intact chorioretinal area in the right eye of verteporfin-infused rabbits, was started 5 minutes after the end of infusion. Three groups were control (dextrose infusion), infusion with verteporfin (left eyes were not irradiated), and irradiation after verteporfin injection (right eyes were irradiated). On the fifth day of the experiment, the eyes were enucleated. The retinas were subsequently frozen and homogenized. Nitrite, a stable end-product of NO and MDA, was measured using the spectrophotometer. Protein concentrations were measured by the Lowry method. Tissue NO and MDA levels were expressed as mu mol/gprt and nmol/mgprt, respectively. Results:The mean retinal NO and MDA levels of the control, infusion, and irradiation groups were 24.67 +/- 6.66, 0.11 +/- 0.02; 45.90 +/- 15.52, 0.21 +/- 0.09; and 84.43 +/- 14.96 mu mol/gprt, 0.58 +/- 0.14 nmol/mgprt, respectively. The mean retinal NO levels were significantly elevated in the infusion and irradiation groups compared with the control group (P:0.004; P:0.001). The mean retinal MDA levels were significantly elevated in the infusion and irradiation groups compared to the control one (P:0.026; P:0.001). Also the mean retinal NO and MDA levels in the irradiation group were found to be significantly higher than the infusion group (P:0.018; P:0.018). Conclusion:Not only PDT, but also verteporfin infusion alone resulted in NO and MDA level increments in the retina, which might be toxic.
Keywords: Malonyldialdehyde; nitric oxide; photodynamic therapy; retina